Implementasi Aplikasi Klinik Pelayanan Rawat Inap dan Rawat Jalan - Nicodias Palasara; Saras Utami; Deny Novianti (STMIK Budi Darma, 2020)
Information technology in the world is developing very fast. This is supported by the existence of electronic devices such as: laptops, telephones and others, with these tools it will make it easier for people to complete their respective jobs. In patient care requires, an information system that supports and provides satisfactory services for patients who visit or seek outpatient treatment and even inpatient care. The clinical system here still uses the manual method, where every time a patient registers, registration officers write patient data in the registration book, write patient medical records and report them. This method will allow for errors in recording, inaccurate reports and delays in finding the required data. With this, the authors create a computerized system that can speed up work, so that patients do not have to wait long and will look more conducive. This information system is created with a web-based program and is assisted by a software, namely sublime